Teacher’s Perspective on Student Center Learning Paradigm in Inclusive Madrasa - Redite Kurniawan; M. Yunus Abu Bakar; Ah. Zakki Fuad (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2023)
Student center learning (SCL) is a paradigm emphasized in the learning approach in the Merdeka Curriculum. Furthermore, the Merdeka Curriculum highlights that differentiated learning must be carried out by teachers in conducting learning. In fact, inclusive madrasahs receive various types of obstacles for students with special needs have implemented differentiated learning with curriculum modifications for students with special needs. The purpose of this study is to analyze the SCL paradigm from the perspective of teachers in inclusive madrasah. The place of this research is MTs. Terpadu Ar-Roihan Lawang Malang which is an inclusive madrasah since 2014. Data were obtained from observations, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusions. Teachers in this madrasah have understood the SCL learning approach and the meaning of learning differentiation even though some teachers still use teacher center learning (TCL) as a learning approach that is more center on the teacher's authority. Interestingly, there is an interchange between TCL and SCL when teachers must deal with students in this inclusive madrasa